MORAL HAZARD INDICATION TOWARDS NON-PERFORMING FINANCING RATIO: A COMPARATIVE STUDY BETWEEN ISLAMIC AND CONVENTIONAL BANKS IN INDONESIA - Anindya Hiroshi Purbayanto, Muhamad
Islamic Banks has been suffering with the NPF problem recent year, whereas conventional banks always maintaining the NPLs below the threshold to keep the bank healthy. The regression of the threshold panel itself is a transformation from a regression of the fixed effect which divides individual observations into regimes. In this study, authors use last-period NPLs ratio as a threshold variable and consider a threshold value of 6.18 percent for Islamic Banks in Model 2 including lagged LGR and 5.84 for conventional banks in Model 2. The result for Islamic banks found the difference behaviour for troubled banks and healthy bank since, there is threshold effect from our fixed effect panel regression. Where for the conventional banks, the result shows different result than the Islamic bank towards the LGR (variable that directly interacted with NPL). The LGR shows opposite way of the Islamic bank result, in Model 1 (benchmark model) shows that LGR negative relationship against NPL, whereas lagged LGR shows opposite way which positive relationship against NPL. Meanwhile, in model 2 LGR of troubled bank and healthy bank have positive relationship against NPL, meaning that its sign that lagged LGR not significantly detect the moral hazard action, because bank with NPLs ratio above the threshold and below the threshold behave similarly. These findings are not consistent with previous study by Zhang et al. (2016) and study that conducted by (Novellyni & Ulpah, 2017). Furthermore, it also a sign that the selected conventional banks have low possibility of moral hazard indications found in the model that authors have done. Finally, all the authors' findings should be the sign that Indonesian Islamic banks are adapting riskier loan strategies which could lead to moral hazard.